Unveiling Diabetic Retinopathy Awareness In Future Medical Professionals: A Study Of The 2022 Class Of Universitas Kristen Krida Wacana, Jakarta - Anindita, Petra Damiana; Siceria, Putri Denova; Benu, Inne Eunike; Ragustri, Jasmine Nazer; Lallo, Ary Kristanto; M, Gabriel; Hendarto, Dino; Anugrahsari, Santi (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2024)
ABSTRACT Background: Diabetes mellitus is a metabolic syndrome with an increasing prevalence and a high mortality rate. One of the microvascular complications that can occur in diabetes mellitus is retinopathy. Diabetic retinopathy is a retinal disorder in patients with diabetes mellitus. This study aimed to determine the description of knowledge about diabetic retinopathy in students of FKIK UKRIDA class of 2022. Methods: This is a descriptive study with a cross-sectional with a total of 99 samples. Sampling by simple random sampling with a questionnaire. The study was conducted at FKIK UKRIDA in October 2022. Results: The study results included 99 respondents. In the univariate analysis, it was observed that 98% of respondents were in their late adolescence, with 59.6% being female and 72.7% having sufficient knowledge. Additionally, the bivariate cross-test results indicated that 70.7% of late teens had sufficient knowledge, while 45.5% of women had sufficient knowledge. Conclusion: The knowledge level of respondents was in the sufficient category, in late adolescence, there was sufficient knowledge among. The frequency distribution based on gender revealed that women with a sufficient knowledge level amounted.